Cross‐sectional survey of awareness and behavioral pattern regarding acne and acne scar based on smartphone application. (4th September 2015) - Park, Seon Yong; Park, Mi Youn; Suh, Dae Hun; Kwon, Hyuck Hoon; Min, Seonguk; Lee, Sang Joo; Lee, Weon Ju; Lee, Mi Woo; Ahn, Hyo Hyun; Kang, Hoon; Lee, Jee Bum; Ro, Young Suck; et al.
Abstract: Background: Although acne scar is a permanent sequela that may be induced by improper management of active acne lesion, patient behavior patterns and awareness regarding acne are unclear. The aim of this study was to identify awareness and behavioral patterns concerning acne and acne scar of people having acne and differences between those with and without acne scars. Methods: The survey was performed via smartphone application for 900 participants in their second to fourth decade having current or previous acne lesions. They were further categorized into two groups based on the presence of acne scar (scar and scarless groups) with no statistical difference in demographic composition. Results: The mean age of all participants was 24.6 ± 5.3. The scar group had a longer disease duration (4.9 years) than those of the scarless group (2.2 years). Participants in the scar group thought that acne scarring affected psychosocial aspects more negatively compared with those in the scarless group. Participants in the scarless group visited dermatology clinics earlier than those in the scar group. In the scar group, 62.1% of participants have never had their acne scars treated medically. Most (88.6%) participants from both groups believed that non‐dermatologic treatment caused side effects or aggravated their acne. Conclusions: Participants with acne scars tended to treat their acne and acne scars improperly, which could negatively affect their daily lives. Acne scars are sequelae of acne and should be regarded as a distinct disease entity, requiring a patient's early visit to dermatologic clinics.